STRATEGI DAKWAH PONDOK PESANTREN MIFTAHUL FALAH DALAM MENINGKATKAN KREATIVITAS SANTRI - Cintia; Devi Fitriani; Wawan Setiawan (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
This research aims to analyze the program, coaching process and results of the Miftahul Falah Islamic boarding school program. This research uses a descriptive method with a qualitative approach. The research results show that the program at the Miftahul Falah Islamic Boarding School consists of daily, weekly, monthly and annual activities. The coaching process is carried out in three stages, including the awareness and behavior formation stage, namely punishment and advice, the ability transformation stage, namely the existence of various programs and facilities for students, the ability improvement stage, namely determining the activity schedule and coaching system. The results of this research show that the missionary strategy of the Miftahul Falah Islamic Boarding School in increasing students' creativity including programs, coaching processes, and program results. The program at the Miftahul Falah Islamic Boarding School is formulated in several long-term and short-term programs, namely daily, weekly, monthly and annual activities. The coaching process is carried out in various stages, namely, first, the stage of awareness and formation of behavior towards behavior. Second, the ability transformation stage in the form of insight, knowledge, skills and skills. The three stages of intellectual ability. Meanwhile, the results of the programs provided can facilitate students to develop interests, talents and gain new insights, especially specialization programs.